Analysis on the Manufacturing of an AA5083 Straight Blade Previously ECAE Processed - Daniel Salcedo; Carmelo Luis; Ignacio Puertas; Javier León; Juan Pablo Fuertes; Rodrigo Luri (Advances in Materials Science and Engineering)
Over these past few years, there have been a large number of technical papers published related to the problem of improving the mechanical properties of materials obtained through severe plastic deformation. Nevertheless, the number of technical papers dealing with improvement in the mechanical properties of mechanical components manufactured from submicrometric grain size material has not been so proficient. Therefore, in this present research work, a straight blade has been manufactured starting from AA-5083 previously processed by ECAE twice (N2) with route C. This material will be manipulated so as to be isothermally forged at different temperature values. This present research work shows the results that are inherent in an improvement in the mechanical properties and the microstructure achieved in the thus obtained components, compared with the starting material. In addition, the optimum forging temperature to achieve these components will be determined. As shown in this research work, it is possible to obtain submicrometric grain size mechanical components with a higher mechanical strength than those obtained in nonultrafine grained materials. The originality of this research work lies in the manufacturing of actual mechanical components from ECAE processed material and the analysis of their properties.